Vitamin C Recycling Regulates Neurite Growth in Neurospheres Differentiated In Vitro - Francisca Espinoza; Rocío Magdalena; Natalia Saldivia; Nery Jara; Fernando Martínez; Luciano Ferrada; Katterine Salazar; Felipe Ávila; Francisco Nualart (MDPI AG, 2020)
The reduced form of vitamin C, ascorbic acid (AA), has been related with gene expression and cell differentiation in the cerebral cortex. In neurons, AA is mainly oxidized to dehydroascorbic acid (DHA); however, DHA cannot accumulate intracellularly because it induces metabolic changes and cell death. In this context, it has been proposed that vitamin C recycling via neuron-astrocyte coupling maintains AA levels and prevents DHA parenchymal accumulation. To date, the role of this mechanism during the outgrowth of neurites is unknown. To stimulate neuronal differentiation, adhered neurospheres treated with AA and retinoic acid (RA) were used. Neuritic growth was analyzed by confocal microscopy, and the effect of vitamin C recycling (bystander effect) in vitro was studied using different cells. AA stimulates neuritic growth more efficiently than RA. However, AA is oxidized to DHA in long incubation periods, generating a loss in the formation of neurites. Surprisingly, neurite growth is maintained over time following co-incubation of neurospheres with cells that efficiently capture DHA. In this sense, astrocytes have high capacity to recycle DHA and stimulate the maintenance of neurites. We demonstrated that vitamin C recycling in vitro regulates the morphology of immature neurons during the differentiation and maturation processes.